A EOUCACÁO CONTEMPORÁNEA, A AMPLlACÁO DO ACESSO A ESCOLA E O SERVICO SOCIAL: notas para debate - Simone Eliza do Canno Lessa (Universidade Federal do Maranhão, 2013)
This article brings a debate about the complex relatlonshlp between Educalion as a public policy and the binding 01the Social Work to it, in particular, its integralion into public school. Shows that exlsts an important and growing debate which atlracts much attention for its recent deepening and expansión 01jobs in the area.